Role of Gamma Knife Radiosurgery in Small Cell Lung Cancer: A Multi-Institutional Retrospective Study of the International Radiosurgery Research Foundation (IRRF). (18th November 2021) - Cifarelli, Christopher P; Vargo, John A; Fang, Wei; Liscak, Roman; Guseynova, Khumar; Warnick, Ronald E; Lee, Cheng-chia; Yang, Huai-che; Borghei-Razavi, Hamid; Maiti, Tonmoy; Siddiqui, Zaid A; Yuan, Justin C; et al.
Graphical Abstract: